A incidência do dolo eventual e da culpa consciente nos crimes de homicídio no trânsito - Dadalto, Bruno Cola (2022)
The present work seeks to analyze the requirements and possibilities of application of concepts of eventual intent and conscious guilt in crimes of homicide committed in the motor vehicle steering. Therefore, it was necessary to demonstrate the importance of the topic raised, as well as the conceptualization of the word "crime" in its formal and material, in addition to exposing the double effect of the penalty that the State intends to achieve by punishing those who commit such illicit conduct, even if in a culpable manner. After overcoming this barrier, a study was carried out and the concepts and theories approached of guilt and deceit, as well as the deepening in the institutes of conscious guilt and eventual fraud, always exposing understandings of jurists and legal scholars. After the necessary explanations to evolve in front of the theme, the central point was reached, where jurisprudence and exemplary cases were exposed that dealt with traffic homicides and raised the incidence of eventual intent and conscious guilt, so that in this way, it would be possible through observation thorough examination of the doctrinal aspects of the institutes, analyze the circumstances and application requirements of the concepts inserted in the mentioned crime. It should be noted that existing data were used, as well as jurisprudential understandings and doctrinal, in line with the inductive method for carrying out the aforementioned search